Protective Effect of Broad Bean Seedling Extract on Parkinson's Disease - Xuecheng LIU; Haojie JIN; Binhui CHEN; Lingyun HE; Taoshi LIU (Shipin gongye ke-ji, 2022)
Objective: To study the protective effect of broad bean seedling extract (BSE) on Parkinson’s disease. Methods: PC-12 and SH-SY5Y cell injury were induced by 50 μmol/L 6-OHDA. The effects of BSE on the proliferation of neuro cells were determined by MTT method. The effects of BSE on reactive oxygen species (ROS), mitochondrial membrane potential and apoptosis in neuro cells were measured. The mouse model of Parkinson’s disease was established by intraperitoneal injection of MPTP, and the mice were divided into blank control group, model control group, 500 mg/kg BSE group, 300 mg/kg BSE group and 25 mg/kg L-dopa group with 6 rats in each group. The effects of BSE on the behavioral function of mice were studied via pole climbing test, rotation test and grip test, and the effects of BSE on the contents of malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in the brain of mice were determined by the test kit. Results: After PC-12 and SH-SY5Y neuro cells were treated by 6-OHDA, the cell proliferation was inhibited, the level of reactive oxygen species increased, the mitochondrial membrane potential decreased and the apoptosis increased. After pretreatment with BSE, the inhibition rate of cell proliferation and the level of reactive oxygen species were significantly decreased, the mitochondrial membrane potential was increased and the apoptosis was inhibited (P<0.01). BSE could significantly shorten the rod climbing time, increase the grip and prolong the rotation time, increase the levels of SOD and GSH-Px in brain tissue, decrease the content of MDA and inhibit lipid peroxidation in brain tissue of MPTP Parkinson’s disease model mice (P<0.01). Conclusion: BSE had a protective effect on nerve cells and can significantly improve the symptoms of Parkinson’s disease in mice. These results suggested that BSE might have potential therapeutic significance for Parkinson’s disease.